Analysis of exchange terms in a projected extended random phase approximation theory applied to the quasielastic (e,e') reaction - Bauer, Eduardo (1998)
A systematic study of the influence of exchange terms in the longitudinal and transverse nuclear response to quasi-elastic (e,e') reactions is presented. The study is performed within the framework of the extended random phase approximation (ERPA), which in conjuction with a projection method permits a separation of various contributions tied to different physical processes. The calculations are performed in nuclear matter up to second order in the residual interaction for which we take a (pi+rho)-model with the addition of the Landau-Migdal g'-parameter. Exchange terms are found to be important only for the RPA-type contributions around the quasielastic peak.